Pengaruh Sudut dan Jari-Jari Saluran Menikung terhadap Konsentrasi Aliran Sedimen Suspensi arah Transversal - Chairul Muharis - (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2017)
The change in channel dimension has a great effect on the flow hydraulic parameters. Likewise, the angle and radius of the bend are not the same will also affect the concentration of suspended sediment flow. To determine the effect of angle and radius of the bend, the measurement of susupended sediment concentration was done at 4 (four) location in Mataram irrigation channel curve. The four locations describe 2 channels having relatively the same angle but having different radius, and 2 (two) channels having the same relative radius but having different angles. Measurement of suspended sediment concentration in tranversal direction is done some depth point used by opcon probe. The results of the research for different angle of bend shows that from the interance to the end of the channel bend so the trend of suspended sediment concentration value are decreases. After the end of the channel bend started there is no more the angle influenced, the trend value of suspended sediment concentration are constant. As for the different radius, the value of suspended sediment concentration is still relatively the same and there is no change significantly. This shows that the relation or influence between the length of the radius of the bend with the value of the suspended sediment concentration is not visible